Short chain fatty acids enhance expression and activity of the umami taste receptor in enteroendocrine cells via a Gα i/o pathway - Shackley,M; Tate,EW; Brown,AJH; Frost,G; Hanyaloglu,AC (2020)
Abstract The short chain fatty acids (SCFAs) acetate, butyrate and propionate, are produced by the fermentation of non-digestible carbohydrates by the gut microbiota. SCFAs are of interest because they regulate appetite, adiposity, metabolism, glycemic control and immunity. SCFAs act at two distinct G protein-coupled receptors (GPCRs), FFAR2 and FFAR3. These are expressed in intestinal enteroendocrine cells (EECs), where they mediate SCFA-driven anorectic gut hormone release. EECs also express other GPCRs that act as nutrient sensors, in a manner that is plastic and adaptable to the environment. SCFAs may elicit some of their health-promoting effects by altering levels of GPCRs in EECs, thus, enhancing gut sensitivity to dietary molecules. Here, we identified that exposure of the murine EEC STC-1 cell-line to a concentration of SCFAs found in the colon, specifically enhances mRNA levels of the umami taste receptors TASR1 and TASR3, without altering levels of the SCFA GPCRs, FFAR2 and FFAR3. Interestingly, treatment of EECs with propionate or butyrate, but not acetate, increased levels of umami receptor transcripts. This phenomenon was reversed by inhibiting Gα i/o signaling with pertussis toxin, suggesting that SCFAs act through FFAR2/3 to alter gene expression. Surprisingly, neither a FFAR3-nor a FFAR2-selective synthetic ligand could increase TASR1/TASR3 mRNA levels. We assessed the functional impact of increases in TASR1/TASR3 expression using unique pharmacological properties of the umami taste receptor; namely, the potentiation of signaling by inosine monophosphate. We found that the umami taste receptor induced inosine-1-phosphate and calcium signaling in response to L-alanine and L-monosodium glutamate, and that butyrate pretreatment significantly enhanced such signaling. Our study reveals that SCFAs may